2007
DOI: 10.1590/s0074-02762007005000037
|View full text |Cite
|
Sign up to set email alerts
|

A population genetics study of Anopheles darlingi (Diptera: Culicidae) from Colombia based on random amplified polymorphic DNA-polymerase chain reaction and amplified fragment lenght polymorphism markers

Abstract: The genetic variation and population structure of three populations of Anopheles darlingi from Colombia were studied using random amplified polymorphic markers (RAPDs) 001). The F ST distances and AMOVAs using AFLP loci support the differentiation of the Guyana biogeographic province population from those of the Chocó-Magdalena. In this last region, Chocó and Córdoba populations showed the highest genetic flow.Key words: amplified fragment length polymorphism -Anopheles darlingi -genetic diversity -malaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
(57 reference statements)
1
15
0
Order By: Relevance
“…Our data agree with previous work conducted on An. darlingi populations from three regions in western and southeastern Colombia, in localities from Antioquia, Chocó, and Meta, 31,32 although those studies did not examine the same molecular markers we examined in our study. Our data also showed that high gene flow among An.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Our data agree with previous work conducted on An. darlingi populations from three regions in western and southeastern Colombia, in localities from Antioquia, Chocó, and Meta, 31,32 although those studies did not examine the same molecular markers we examined in our study. Our data also showed that high gene flow among An.…”
mentioning
confidence: 94%
“…darlingi populations from northwestern (Córdoba), western (Chocó) and southern Colombia (Meta), using amplified fragment length polymorphism (AFLP) and RAPDs estimated F ST values that were congruent with high gene flow among western populations (Córdoba and Chocó) and suggested that the overall genetic differences observed (RAPD F ST = 0.084, AFLP F ST = 0.229) could be attributed to the biogeographic characteristics of each particular region. 31,32 Previous studies have made significant contributions to the population structure, evolutionary processes and demographic history of An. darlingi .…”
Section: Introductionmentioning
confidence: 99%
“…González et al (2007) found average values of 0.374 and 0.309 with RAPD and Genetic differences in Anopheles darlingi AFLP markers, respectively. Santos et al (1999) found values ranging from 0.290 to 0.375 for populations of different states of Brazil.…”
Section: Discussionmentioning
confidence: 92%
“…González et al (2007) give estimates of within population variation of 92%, using RAPD markers, and 77% with AFLP, in populations of A. darlingi in Colombia. It must be noted that the sampled populations are not only much more distant than ours, but they are separated by mountains.…”
Section: Discussionmentioning
confidence: 99%
“…RAPD-polymerase chain reaction (PCR) is a technique that generates markers by the amplification of random DNA segments with single primers of arbitrary nucleotide sequence (Williams et al, 1990). These molecular markers have been successfully used in genetic variability studies; they were applied to natural populations of different mosquito species including Aedes albifasciatus (de Sousa et al, 1999), Aedes (Finlaya) japonicus (Fonseca et al, 2001), Aedes albopictus (Ayres et al, 2002), Anopheles nuñeztovari (Posso et al, 2003), Anopheles superpictus and Anopheles pulcherrimus (Abramova et al, 2005), Anopheles darlingi (González et al, 2007), and Aedes aegypti (Julio et al, 2009). However, there are no reports of studies performed on the genetics of O. taeniorhynchus populations on the Colombian Atlantic coast using these types of markers.…”
Section: Introductionmentioning
confidence: 99%